Effectiveness of generative learning strategies based on mobile learning technologies in higher education - Kravchenko, Olena; Dokuchaieva, Viktoriia; Sbitnieva, Liudmyla; Sakhatska, Vita; Akinshyna, Iryna (International Journal of Evaluation and Research in Education (IJERE), 2024)
The paper aims to comprehensively assess the effectiveness of generative learning strategies (GLS) using mobile learning technologies (MLT) in higher education, based on a quasi-experiment and quantitative and qualitative analysis. Methods included concept mapping, round table discussions, monitoring, computer testing, and statistical analysis. GLS with MLT demonstrated enhanced performance in Practical Ukrainian and English Language Courses. MLT-based GLS optimized teacher workload by reducing assignment checking time. Respondents rated MLT-based GLS for Ukrainian/English at 7.8/10. Effective methods included self-review, text correction, and concept mapping. The study validates MLT-based GLS in higher education, improving student performance and easing teacher tasks. Further research is planned for literature studies.